Communication systems and networks : 9th International Conference, COMSNETS 2017, Bengaluru, India, January 4-8, 2017, Revised selected papers and invited papers /: 9th International Conference, COMSNETS 2017, Bengaluru, India, January 4-8, 2017, Revised selected papers and invited papers. (2017) - Unknown
No abstract available